Forecast Error Calculation with Mean Squared Error (MSE) and Mean Absolute Percentage Error (MAPE) - Ansari Saleh Ahmar (JINAV: Journal of Information and Visualization, 2020)
Calculation errors in forecasting a data are very important from a forecasting process. The high level of forecasting accuracy will affect the level of confidence in forecasting decision making.